A PENGARUH CELEBRITY ENDORSEMENT, SOCIAL MEDIA MARKETING DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN PILOTTER GANK (Studi Pada Konsumen Pilotter Gank di Gempol) - Dino Taufiq Redyansyah; M Sulhan (Jurnal Ilmu Administrasi dan Bisnis, 2026)
This study aims to determine the influence of celebrity endorsement, social media marketing, and lifestyle on purchasing decisions for Pilotter Gank products in Gempol, both partially and simultaneously. The background of this study is based on the increasing trend of social media use and the role of celebrities in promoting local brands, as well as the importance of lifestyle as a factor in consumer decision making. This type of research is quantitative with a causal approach. Data were collected by distributing questionnaires to 119 respondents who were Pilotter Gank consumers in the Gempol area. The analysis technique used was multiple linear regression analysis with the help of SPSS version 25. The results of the study showed that partially the variables celebrity endorsement, social media marketing, and lifestyle had a significant effect on purchasing decisions. This is evidenced by the results of the T Test which showed a significant value of 0.000 <0.05. Simultaneously, the three variables also have a significant effect on purchasing decisions as evidenced by the results of the F Test obtaining a significant value of 0.000 <0.05.